Qué significa pensar durante la producción de la obra de arte en la serie Línea-miento de política territorial internacional (2020)
This article explores the meaning of thinking from an artistic practice which opens a dialogue with the truth that the production of the work presents. Based on two texts by Heidegger "What is called thinking" and "The origin of the work of art" this process of thought is analyzed, during the production of the series "Borderland Guide-line. This analysis shows the way of thinking, during the production of the work, disassemble the representation of concepts such as limit, edge, border, and margin, and allows the truth of these concepts, as a work, it is going to be revealed, as the artist has aesthetic experiences with what the work will be.